Assessment of Bioactivity of Some Plant Species in Bac Huong Hoa Nature Reserve and Its Neighbourhood in Quang Tri Province - Lee, Changyoung; Bach, Tran The; Hai, Do Van; Quang, Bui Hong; Ha, Bui Thu; Thanh, Nguyen Trung; Thuy, La Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1, 2019)
This paper studies the bioactivity of the plant species collected from Bac Huong Hoa Nature Reserve and its neighbourhood. The paper identifies 15 anti-cancer cell lines species of 15 families, namely Annonaceae, Apocynaceae, Aquifoliaceae, Araliaceae, Asteraceae, Clusiaceae, Euphorbiaceae, Flacourtiaceae, Hernandiaceae, Verbenaceae, Myrsinaceae, Myrtaceae, Theaceae, Thymelaeaceae, and Zingiberaceae.  Seven out of these species belong to the anti-1 cancer cell lines, including Strophanthus perakensis Scort. ex King & Gamble, Ilex cochinchinensis (Lour.) Loes., Garcinia benthamii Pierre, Ostodes paniculata Blume, Syzygium syzygioides (Miq.) Merr. & L.M. Perry, Camellia furfuracea (Merr.) Cohen-Stuart, and Linostoma decandrum (Roxb.) Wall. ex Meisn.; 4 anti-2 cancer cell lines species: Tithonia diversifolia (Hemsl.) A. Gray, Illigera parviflora Dunn, Callicarpa arborea Roxb., and Alpinia napoensis H. Dong & G.J. Xu; 3 anti-3 cancer cell lines species: Annona glabra L., Trevesia sphaerocarpa Grushv. & N. Skvorts., and Myrsine   seguinii  H. Levl. ; 1 anti-4 cancer cell lines species, Casearia membranacea Hance; 1 anti-A549 lung cancer species, Myrsine   seguinii  H. Levl. Fifty species of 30 families with anti-inflamatory activities, of which, 5 species with high anti-inflamatory activities, including Myrsine seguinii Levl. (Myrsinaceae), Croton kongensis Gagnep. (Euphorbiaceae), Ilex cochinchinensis (Lour.) Loes. (Aquifoliaceae), Trevesia sphaerocarpa Grushv. & N. Skvorts. (Araliaceae) and Garcinia benthamii Pierre (Clusiaceae). These findings can provide guidance in studying medicinal plants in Bac Huong Hoa Nature Reserve and remedies of Van Kieu ethnic group. Keywords Bac Huong Hoa Nature Reserve, bioactivity, plants, Van Kieu ethnic group. References [1] Nguyễn Tiến Bân (chủ biên) và cs, Danh lục các loài thực vật Việt Nam, tập 2, 3, NXB Nông nghiệp, Hà Nội, 2003 - 2005. [2] Phạm Hoàng Hộ, Cây cỏ Việt Nam (3 quyển), NXB Trẻ, Thành phố Hồ Chí Minh, 1999 - 2000. [3] Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, NXB Đại học Quốc gia Hà Nội, Hà Nội, 2007. [4] Nguyễn Thị Duyên, Nghiên cứu thành phần hóa học và tác dụng sinh học của cây Bảy lá một hoa - Paris polyphylla var. chinensis Franchet thu thập tại Việt Nam, Luận án Tiến sĩ hóa học, 2017. [5] Phạm Đức Thắng, Nghiên cứu cấu trúc và hoạt tính sinh học một số hợp chất phân lập từ cây Cọ hạ long - Livistona halongensis T.H. Nguyen & Kiew và cây Rau má - Centella asiatica (Linn.) Urban, Luận án tiến sĩ hóa học, 2012. [6] Mai Hùng Thanh Tùng, Nghiên cứu thành phần hóa học và hoạt tính sinh học của hai loài Khổ sâm mềm - Brucea mollis Wall. ex Kurz và Cơm rượu trái hẹp - Glycosmis stenocarpa (Drake) Guillaum) ở Việt Nam, Luận án tiến sĩ hóa học, 2012. [7] Tôn Nữ Liên Hương, Khảo sát thành phần hóa học và một số hoạt tính sinh học của hai cây Rau má lá sen - Hydrocotyle bonariensis Comm. ex Lam. và Hydrocotyle vulgaris L. (Apiaceae), Luận án tiến sĩ hóa học, 2013. [8] K.H. Kim, E.J. Kim, M.J. Kwun, T.T. Bach, S.M. Eum, J.Y. Choi, S. Cho, S.J. Kim, S.I. Jeong, M. Joo, Suppression of lung inflammation by the methanol extract of Spilanthes acmella Murray is related to differential regulation of NF-κB and Nrf2, Journal of Ethnopharmacology. 217 (2018) 89.